2007
DOI: 10.1677/jme-07-0094
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-II acute regulation of rapid response genes in human, bovine, and rat adrenocortical cells

Abstract: Angiotensin-II (Ang-II) regulates adrenal steroid production and gene transcription through several signaling pathways. Changes in gene transcription occur within minutes after Ang-II stimulation, causing an increase in aldosterone production and subsequent increase in the overall capacity to produce aldosterone. Our goal was to compare the Ang-II regulation of early gene expression and confirm the up-regulation of selected genes using quantitative real-time RT-PCR (qPCR) across three species, such as, human, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 65 publications
5
53
2
Order By: Relevance
“…Herein, we further determine the downstream signaling events that inhibit CYP17. Based on previous observations indicating FOS as a rapid-response gene activated by Ang II (Nogueira et al, 2007), and on the observation that protein synthesis was needed for TPA inhibition of CYP17, we wanted to determine if FOS induction could be dependent on PKC activation. Our microarray analysis and time- course study revealed the ability of TPA, as well as of Ang II, to induce elevated FOS expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, we further determine the downstream signaling events that inhibit CYP17. Based on previous observations indicating FOS as a rapid-response gene activated by Ang II (Nogueira et al, 2007), and on the observation that protein synthesis was needed for TPA inhibition of CYP17, we wanted to determine if FOS induction could be dependent on PKC activation. Our microarray analysis and time- course study revealed the ability of TPA, as well as of Ang II, to induce elevated FOS expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that the synthesis of new proteins is required for TPA-mediated inhibition of CYP17. We have previously shown that Ang II mediates FOS induction in adrenal cells (Nogueira et al, 2007). Because PKC is activated by Ang II after binding its receptor, we proposed that FOS could also be a factor regulated by TPA.…”
Section: Activation Of Pkc Induces Fos Expression In H295r Cellsmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been well established that AngII can stimulate mRNA expression of NGFIB, NURR1, and NOR1 [5,18,19]. However, K + responsiveness of this gene family remains unclear [20,21].…”
Section: The Orphan Nuclear Receptor Ngfib Family Members Do Not Incrmentioning
confidence: 99%